Competição larval e variação de história de vida em Acanthoscelides macrophthalmus (Coleoptera: Chrysomelidae: Bruchinae) - Cesar, Cassia de Souza Siqueira [UNIFESP] (2018)
Intraspecific competition for resources during development and differences in resource quality may affect some life history traits of individuals. Adjustments in life history traits can be expressed by changes in body size, influencing sexual size dimorphism (SSD), as well as changes in fecundity, offspring size and survival. The present study aimed to investigate whether larval competition and interpopulational quality variation of Leucaena leucocephala seeds affects life history traits and SSD in Acanthoscelides macrophthalmus. Fruits of two L. leucocephala populations, containing seeds of different sizes, were collected, establishing control populations in the laboratory. With those insects that emerged from seeds of smaller sizes, couples were formed. Half of them were reared on seeds of its own population and the other half were reared on the larger seeds. The seeds containing one egg and two or more eggs were removed and separated, establishing two treatments for each population: larvae growing on the presence or the absence of competition. The fecundity, egg size, survival, body size and SSD of the individuals were determined for each treatment. Seed quality of the two populations was estimated by determining seed hardness, biomass, water content, carbon/nitrogen ratio and the percentages of hydrogen and sulfur. The results showed that the smaller seeds presented better quality than the larger seeds. Although there was no difference in body size and SSD, when individuals of A. macrophthalmus developed on seeds of better quality and were under competition, they invested more in fecundity. However, when they developed on seeds of poor quality and were also under competition, they invested more in survival during the adult stage. A trade-off between egg size and number was also observed. Females from the population with smaller seeds laid more eggs but smaller in size. On the other hand, the females from the population with larger seeds laid fewer eggs but larger in size.